GOLPH2 expression in renal cell cancer - Jung Klaus; Moch Holger; Dietel Manfred; Riener Mark-Oliver; Fritzsche Florian; Kristiansen Glen (BMC Urology, 2008)
Abstract Background Renal cell carcinomas (RCC) are among the most common and most lethal genitourinary malignancies. GOLPH2 (golgi phosphoprotein 2, GOLM1) has recently been proposed as a biomarker for hepatocellular and prostate cancer. In this study we analysed the expression patterns and the prognostic and diagnostic value of GOLPH2 in RCC. Methods GOLPH2 protein expression was analysed by immunohistochemistry in 104 clinically well characterized RCC cases in comparison with matched normal kidney tissue and in association with clinico-pathological parameters. Statistical analyses including Kaplan Meier analyses were performed with SPSS version 15.0. Results GOLPH2 was highly expressed in normal renal tubules and in almost half of RCC with a statistically significant predominance in the papillary and chromophobe histological subtypes. No other associations with clinico-pathological parameters were detectable. The Kaplan-Meier curves showed a weak trend for unfavourable prognosis of tumours with high GOLPH2 expression, but failed significance. Conclusion GOLPH2 protein is expressed in normal renal tissue (especially in distal tubular epithelia) and is down-regulated in the majority of clear cell RCC. In papillary and chromophobe RCC GOLPH2 expression is consistently present. In contrast to its diagnostic value in hepatocellular and prostatic carcinomas, a prognostic or diagnostic value of GOLPH2 in RCC appears to be unlikely.